Poets and Playwrights : Shakespeare, Jonson, Spenser, Milton - Stoll, Elmer Edgar, 1874-1959 (Book collections on Project MUSE., 2014)
Poets and Playwrights was first published in 1967. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. Poets and Playwrights is a collection of nine essays by the eminent Shakespearean scholar and critic, the late Elmer Edgar Stoll. In this work, which was first published by the University of Minnesota Press in 1930, Professor Stoll presents his maturest consideration of the art of the poets and playwrights of his subtitle--Shakespeare, Jonson, Spenser, and Milton. The most extensive essay, "Shakespeare and the Moderns," includes, in Mr. Stoll's words, "a review of Shakespeare as I conceive him, in order the better to compare him with those who in some respect or other are his peers."